Methadone for Pain Relief. (2nd April 2016) - Johnson, Joseph; Sheth, Samir
ABSTRACT: Questions from patients about pain conditions and analgesic pharmacotherapy and responses from authors are presented to help educate patients and make them more effective self-advocates. In reply to a question, the authors discuss the use of methadone for pain management, outline how the body processes methadone, list interactions and side effects, and emphasize the importance of taking the medication as prescribed.